POTENSI PROBIOTIK DADIAH TERHADAP KADAR KOLESTEROLTOTAL TIKUS PUTIH JANTAN GALUR WISTAR (RATTUS NORVEGICUS) - SA, Evasha; Abdullah, Dessy; Zulkarnaini, Aryaldy (Nusantara Hasana Berdikari, 2022)
Dadiah is a fermented buffalo milk product from traditional food. The positive impact of probiotics in humans increases resistance in the digestive system. It lowers cholesterol—this study aimed at the effect of probiotics on total cholesterol levels in white male rats. The research method used a true experiment with a post-test randomized control group design. The sample used Wistar strain male white rats (Rattus norvegicus) aged 8-12 weeks and weighing 250-300 grams. Samples were taken in four groups randomly with 28 rats—processing using One Way ANOVA and LSD. The mean total cholesterol levels in rats (K +) were 100.85 mg /dL. (K-), namely 205.28 mg / dL Group P1 and P2, namely 170.28 mg / dL and 158.28 mg / dL. The largest decrease in cholesterol levels compared to (K +) was in the P2 group. The mean blood sugar levels in the group (K +) 85.71 mg / Dl, (K-), at P1 curd was 1.87g, namely 87 mg / dL, and at P2 curds 3.74 g was 102.71 mg / dL. The greatest decrease in cholesterol levels compared to (K +) was at P1. There was an effect of curd probiotic on total cholesterol levels of white male rats with (P <0.05). The conclusion was that curd probiotic's effect on total cholesterol levels of white male rats.